Social media-based community science for turtle nest monitoring and conservation - Marc Dupuis-Désormeaux; Grace Van Alstyne; Maureen Mueller; Ruth Takayesu; Vince D'Elia; Tisha Tan; Suzanne E. MacDonald (Canadian Science Publishing, 2024)
In late 2020, a private volunteer group operating through a Facebook group approached Toronto and Region Conservation Authority (TRCA) with an interest in participating in the Citizen Science Nest Protection and Monitoring Volunteer Program. During the 2021 season, TRCA staff virtually trained volunteers in turtle nest detection, protection, and monitoring due to COVID-19 social constraints, and provided necessary supplies and equipment. In 2021 volunteers and staff detected 181 turtle nests and were able to protect 75 nests with simple predator-exclusion devices, while in 2022, 165 nests were detected, and 155 were protected. The volunteers also collected data, including nesting location, date, and species in addition to the number of successful hatchlings (2021 only). In 2021, the 75 protected nests yielded 81 Midland Painted Turtle and 665 Snapping Turtle hatchlings. Five Midland Painted Turtle's eggs were also recovered from an injured turtle, and 44 Snapping Turtle eggs were recovered from a partially predated nest, transported to the Ontario Turtle Conservation Centre, incubated, hatched, and overwintered, and then released back into the local wetlands. The partnership with a local community group proved effective, and we would recommend this practice to other conservation organizations interested in turtle nest protection.